A novel conserved phosphotyrosine motif in the Drosophila fibroblast growth factor signaling adaptor Dof with a redundant role in signal transmission. - Csiszar, A.; Vogelsang, E.; Beug, H.; Leptin, M. (Molecular and Cellular Biology, 2010)
The fibroblast growth factor receptor (FGFR) signals through adaptors constitutively associated with the receptor. In Drosophila melanogaster, the FGFR-specific adaptor protein Downstream-of-FGFR (Dof) becomes phosphorylated upon receptor activation at several tyrosine residues, one of which recruits Corkscrew (Csw), the Drosophila homolog of SHP2, which provides a molecular link to mitogen-activated protein kinase (MAPK) activation. However, the Csw pathway is not the only link from Dof to MAPK. In this study, we identify a novel phosphotyrosine motif present in four copies in Dof and also found in other insect and vertebrate signaling molecules. We show that these motifs are phosphorylated and contribute to FGF signal transduction. They constitute one of three sets of phosphotyrosines that act redundantly in signal transmission: (i) a Csw binding site, (ii) four consensus Grb2 recognition sites, and (iii) four novel tyrosine motifs. We show that Src64B binds to Dof and that Src kinases contribute to FGFR-dependent MAPK activation. Phosphorylation of the novel tyrosine motifs is required for the interaction of Dof with Src64B. Thus, Src64B recruitment to Dof through the novel phosphosites can provide a new link to MAPK activation and other cellular responses. This may give a molecular explanation for the involvement of Src kinases in FGF-dependent developmental events.